1989
DOI: 10.1366/0003702894202760
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Studies of “Hard” and “Soft” Woods

Abstract: FT-IR spectra of 24 different woods have been studied with the use of whole wood pieces and a diffuse reflectance accessory. Three absorptions have been identified, the positions or relative intensities of which are characteristic of the holocellulose/lignin ratio or of the type of lignin present in the wood. These spectral features serve as useful indicators to distinguish between “soft” or “hard” woods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(93 citation statements)
references
References 6 publications
2
89
0
2
Order By: Relevance
“…This approach has been extensively studied (Pandey and Pitman 2003;Li et al, 2011;Shang et al 2013). Different spectrum peaks were studied for holocellulose (cellulose and hemicellulose (Owen and Thomas 1989;Bodîrlau and Teaca 2009;Li et al 2011).…”
Section: Decay Testmentioning
confidence: 99%
“…This approach has been extensively studied (Pandey and Pitman 2003;Li et al, 2011;Shang et al 2013). Different spectrum peaks were studied for holocellulose (cellulose and hemicellulose (Owen and Thomas 1989;Bodîrlau and Teaca 2009;Li et al 2011).…”
Section: Decay Testmentioning
confidence: 99%
“…In the spectrum of the blank spruce (not irradiated, curve b), the absorption centred at 1507.3 cm -1 is due to lignin, while the weak absorption centered at 1730.7 cm -1 is a polysaccharide vibration (C = O stretch in non-conjugated ketones, carbonyl and ester groups) (Owen and Thomas 1989;Müller et al 2003). The UV irradiation leads to significant changes in the FT-IR spectra of the wood surface without coating (curve c).…”
Section: Resultsmentioning
confidence: 99%
“…The disappearance of the band at 1,738 cm -1 revealed that alkaline treatment cleaved the ester bonds of hemicelluloses, such as acetyl and uronic-ester groups in all of the alkali-treated samples (Sun and Tomkinson, 2002). Two apparent bands were detected in the case of untreated substrates around 1,735 and 1,241 cm -1 attributable to C = O and C-O stretching vibrations at the acetyl ester unit of hemicelluloses (Owen and Thomas, 1989;Chen et al, 1997;Gastaldi et al, 1998;). However, a gradual diminishing of intensities in the two bands in both the hydrothermally and NaOH pretreated substrates was ascribed to the deacetylation with the removal of hemicelluloses.…”
Section: Ft-ir Analysismentioning
confidence: 95%